Veterinary Viewpoints, No. 3, 1989 - Cornell University. College of Veterinary Medicine; Redmond, Karen (Cornell University. College of Veterinary Medicine, 1989)
Topics in this issue include: Transgenic Animals By Next Decade: International Symposium Highlights Progress (Metta Winter, William Hansel); [Obituary] A. Gordon Danks; Alumni Profile: Practitioner Earns Research Award (Barry A. Lissman); Alumni Awards; Five Decades of Applications: Applicants for Admission 1934-1989; In The James Law Tradition [James Law Professorships] (Bud C. Tennant, Robert H. Wasserman); Fatal Syndrome Studied in Salmon (Jan Spitzbergen); International Exchange Agreement; Design Phase of New Facilities to Begin; Life & Work in China: A Personal View (Hung-Chang Wang); Fogarty International Fellowship Awarded: Gleed to Study Low Blood Oxygen (Robin Gleed); Reunion Rider (Leo Dube); Mammoth Bones Tell Story of Age (Lennart Krook).